Columnar Liquid‐Crystalline Dibenzopentacenodithiophenes by Photocyclization. Issue 24 (3rd May 2016) - Cabral, Marilia G. Belarmino; Pereira de Oliveira Santos, Deise M.; Bentaleb, Ahmed; Hillard, Elizabeth A.; Cristiano, Rodrigo; Gallardo, Hugo; Durola, Fabien; Bock, Harald
Abstract: The twofold glyoxylic Perkin reaction of perylene‐3, 9‐diglyoxylic acid with thiophene‐diacetic acid followed by oxidative photocylization and reaction with α‐branched primary alkylamines yields columnar liquid‐crystalline diimides with two sulfur atoms in the condensed arene system. A broad temperature range of the hexagonal columnar mesophase is induced by racemic doubly branched alkyl chains. The HOMO and LUMO energy levels of these thiophene‐derived diimides qualify them as electron donors with respect to perylene diimides. Abstract : In four straightforward steps from perylenediglyoxylic acid—Perkin coupling, esterification, photooxidation, imidification—red polycyclic doubly thiophene‐substituted diimides are accessible. These stack in columnar liquid crystal and crystal structures and are electronically complementary to common electron acceptors such as perylene diimides.